Desmigratif Program: Implementation Evaluation and Policy Recommendations for Sustainability Enhancement - Nuzula, Firdausi; Roza, Hendry; Hazami, Muhammad Fikrie (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2024)
The Desmigratif Program is an initiative of the Indonesian government to provide protection and empowerment for Indonesian Migrant Workers (PMI). Based on the evaluation results, the Desmigratif Program has had a positive impact on the welfare of PMI and their families. Several aspects that are the focus of the evaluation include the effectiveness of migration services, the sustainability of productive businesses, involvement in community parenting, and the role of cooperatives and BUMDes in supporting the local economy. The evaluation shows that coordination between actors at the local and central levels is key to the success of the program. However, the evaluation also noted several challenges faced, such as limited human resources and lack of supporting technological infrastructure. The success of the Desmigratif Program is highly dependent on the synergy between local governments, communities, and the private sector. Strong regulatory support, adequate budget allocation, and increased community capacity and participation are key to the sustainability of the program. Routine evaluation and ongoing technical guidance are also important to ensure that the program can continue to grow and provide benefits to retired PMI and their families.